Thermolysis of High-Density Polyethylene to Petroleum Products. (30th May 2013) - Kumar, Sachin; Singh, R. K.
Abstract : Thermal degradation of plastic polymers is becoming an increasingly important method for the conversion of plastic materials into valuable chemicals and oil products. In this work, virgin high-density polyethylene (HDPE) was chosen as a material for pyrolysis. A simple pyrolysis reactor system has been used to pyrolyse virgin HDPE with an objective to optimize the liquid product yield at a temperature range of 400°C to 550°C. The chemical analysis of the HDPE pyrolytic oil showed the presence of functional groups such as alkanes, alkenes, alcohols, ethers, carboxylic acids, esters, and phenyl ring substitution bands. The composition of the pyrolytic oil was analyzed using GC-MS, and it was found that the main constituents were n-Octadecane, n-Heptadecane, 1-Pentadecene, Octadecane, Pentadecane, and 1-Nonadecene. The physical properties of the obtained pyrolytic oil were close to those of mixture of petroleum products.